Practices for grading and evaluating student teachers in public primary teacher training institutions in the Philippines - Rungsayapun, Kosintr 1938- (s.n.], 1966)
The author conducted a survey of the practices for grading and evaluating student teachers in seven public elementary teacher training institutions of the Philippines. This survey includes the existing practices for grading and evaluating student teachers in both on- and off-campus student teaching and the practices that are suggested to be modified and improved.